Impact of mononuclear cell infiltration on chondrodestructive MMP/ADAMTS production in osteoarthritic knee joints-an ex vivo study - Platzer, Hadrian; Nees, Timo A.; Reiner, Tobias; Tripel, Elena; Gantz, Simone; Hagmann, Sébastien; Moradi, Babak; Rosshirt, Nils (Journal of Clinical Medicine, 2020)
Progressive loss of joint function in osteoarthritis (OA) is driven by degenerative and inflammatory processes and their complex interaction. Decoding the link between degeneration and inflammation is one of the most exciting approaches in understanding OA pathophysiology and holds the promise to open new therapeutic avenues. The overarching goal of this project was to analyze the impact of mononuclear cells (MNC) on enzymatic chondrodestructive processes (MMP/ADAMTS) in OA. Synovial membrane (SM), articular cartilage (AC) and peripheral blood (PB) were obtained from a total of 21 patients with advanced knee OA who underwent arthroplastic surgery. In supernatants of native synovial cell cultures, T cell-depleted synovial cell cultures and macrophage-depleted synovial cell cultures, the concentrations of various metalloproteinases were examined by Enzyme Linked Immunosorbent Assay (ELISA). Furthermore, ELISA was used to analyze concentrations of metalloproteinases in supernatants of chondrocyte monocultures and chondrocyte co-cultures with CD4(+)CD127(dim/-) enriched peripheral blood mononuclear cells (PBMC), Treg depleted CD4(+)CD25(-)CD127(dim/-) enriched PBMC and CD4(+)CD25(+)CD127(dim/-) Treg. Compared to native synovial cell culture, T cell depletion led to significantly lower levels of MMP-1, MMP-3 and MMP-9 and macrophage depletion led to a significant decline of MMP-1, MMP-3, MMP-9 and ADAMTS-5 concentration. Compared to T cell depletion, macrophage depletion resulted in a significantly stronger reduction of MMP-1, MMP-3, MMP-9 and ADAMTS-5. In chondrocyte co-culture with CD4(+)CD127(dim/-) enriched PBMC the concentration of MMP-1 and ADAMTS-5 was significantly increased compared to chondrocyte monoculture. No significant differences were found between chondrocyte monoculture and chondrocyte co-culture with Treg as well as between co-culture with CD4(+)CD127(dim/-) enriched PBMC containing Treg and co-culture with Treg-depleted CD4(+)CD25(-)CD127(dim/-) enriched PBMC. In conclusion, our data suggests that both synovial macrophages and T cells have a catabolic potential by inducing the release of chondrodestructive metalloproteinases in OA synovium. This study also supports the hypothesis that MNC affect the release of metalloproteinases by chondrocytes and are hereby involved in the cartilage-induced chondrodestructive process. In this study no suppressive effect of Treg was shown.
Gesehen am 06.07.2020